The Effect of Using Fast Roast and Slow Roast Roasting Techniques on the Chemical and Organoleptic Characteristics of Robusta Coffee Beans (Coffea robusta L.) - Santoso, Aji; Slameto, Slameto; Savitri, Dyah Ayu; Kusbianto, Dwi Erwin; Suud, Hasbi Mubarak (Food, Agriculture and Natural Resources - NETWORKS, 2024)
One of the commodities with the highest economic value in the plantation sector in Indonesia is coffee. In 2016 there was a significant difference between the area of robusta and arabica coffee, with the area of robusta coffee being superior. The wide difference between robusta and arabica coffee plantations is because robusta coffee is considered a potential opportunity in developing the community's economy compared to arabica coffee with a particular market. To improve the taste or quality of coffee production, one of the factors is the roasting process. Currently, the demand for coffee production is increasing with the need for maximum quality and taste of coffee beans, so the processing of coffee plants must be very concerned and improved. Therefore this study aims to determine the roasting technique with a roasting machine and its effect on improving the quality and taste of coffee beans that are popular with consumers. This study used a Split Plot Design (SPD) using the basic pattern of a completely Randomized Design consisting of 2 levels. The first factor is the roasting time as the main plot with four levels. Then the second factor is the roasting temperature with two levels. Each factor was repeated four times so there were 32 experimental units. The results of this study indicate that in the roasting process using slow roast and fast roast techniques, roasting time affects all observation parameters, namely moisture content, pH value, brix value, flavor, aroma, and caffeine. However, the roasting temperature only affects moisture content, brix value, and caffeine.